ANALYSIS OF FINANCIAL PERFORMANCE AND COMPANY SHARES BEFORE AND AFTER SEASONED EQUITY OFFERINGS - Bintang Arhya Wisesha Susilo; Dodik Ariyanto (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
Seasoned Equity Offerings (SEO) is a company strategy to increase capital by issuing new shares to existing investors. The goal of this study is to evaluate the financial success of the corporation prior to and following search engine optimization (SEO) by examining indicators such as current ratio, debt to equity ratio, return on assets, price to book value, and stock returns. This research uses secondary data from 76 companies listed on the Indonesia Stock Exchange (BEI) that carried out SEO in the 2017-2021 period. Data were analyzed using descriptive statistics, the Kolmogorov-Smirnov normality test and the Wilcoxon Signed Rank Test to see notable differences between financial performance and stock performance before and after SEO. The research results show that there are significant differences in the proxies for current ratio, dept to equity ratio, price to book value and stock returns after SEO, but there are no significant differences in the proxies for return on assets.